Chronic activation of anti‐oxidant pathways and iron accumulation in epileptogenic malformations. (14th January 2020) - Zimmer, T. S.; Ciriminna, G.; Arena, A.; Anink, J. J.; Korotkov, A.; Jansen, F. E.; van Hecke, W.; Spliet, W. G.; van Rijen, P. C.; Baayen, J. C.; Idema, S.; Rensing, N. R.; et al.
Abstract : Aims: Oxidative stress is evident in resected epileptogenic brain tissue of patients with developmental brain malformations related to mammalian target of rapamycin activation: tuberous sclerosis complex (TSC) and focal cortical dysplasia type IIb (FCD IIb). Whether chronic activation of anti‐oxidant pathways is beneficial or contributes to pathology is not clear. Methods: We investigated oxidative stress markers, including haem oxygenase 1, ferritin and the inflammation associated microRNA‐155 in surgically resected epileptogenic brain tissue of TSC ( n = 10) and FCD IIb ( n = 8) patients and in a TSC model ( Tsc1 GFAP−/− mice) using immunohistochemistry, in situ hybridization, real‐time quantitative PCR and immunoblotting. Using human foetal astrocytes we performed an in vitro characterization of the anti‐oxidant response to acute and chronic oxidative stress and evaluated overexpression of the disease‐relevant pro‐inflammatory microRNA‐155. Results: Resected TSC or FCD IIb tissue displayed higher expression of oxidative stress markers and microRNA‐155. Tsc1 GFAP−/− mice expressed more microRNA‐155 and haem oxygenase 1 in the brain compared to wild‐type, preceding the typical development of spontaneous seizures in these animals. In vitro, chronic microRNA‐155 overexpression induced haem oxygenase 1, iron regulatory elements and increased susceptibility to oxidative stress. Overexpression of iron regulatory genes was also detected in patients with TSC, FCD IIb and Tsc1 GFAP−/− mice. Conclusion: Our results demonstrate that early and sustained activation of anti‐oxidant signalling and dysregulation of iron metabolism are a pathological hallmark of FCD IIb and TSC. Our findings suggest novel therapeutic strategies aimed at controlling the pathological link between both processes.